Epstein–Barr Virus Circulating Tumor DNA (ctDNA) as a Biomarker in Nasopharyngeal Carcinoma: A Narrative Review - Vemas Rifki Pradana; Dila Septianing Nugrahanifa; Arsya Sakti Yudha; Faza Ovita Balqis; Fadhil Emdian Nugraha; Safari Wahyu Jatmiko (UMSU, 2026)
Nasopharyngeal carcinoma (NPC) is a cancer with a characteristic distribution in East and Southeast Asia, including Indonesia, with an incidence of 4.7 cases per 100,000 population per year. Conventional diagnostic methods still have limitations because they are invasive, carry a risk of false negatives, and are not suitable for repeated monitoring. Liquid biopsy using Epstein-Barr virus circulating tumor DNA (EBV-ctDNA) offers great potential as a noninvasive biomarker for the diagnosis and management of NPC. This narrative review was conducted through a literature search on PubMed and Google Scholar (2020–2025) using keywords related to NPC, EBV-ctDNA, and liquid biopsy. Of the 314 articles identified, 14 publications were selected based on inclusion and exclusion criteria. The results showed that EBV-ctDNA has a sensitivity of up to 97% in detecting NPC and plays a role in early diagnosis, risk stratification, therapeutic response monitoring, and earlier recurrence detection compared to imaging modalities. Digital PCR and next-generation sequencing technologies improve detection accuracy and enable large-scale population screening applications. EBV-ctDNA has the potential to be a transformative biomarker with high sensitivity and specificity, supporting routine clinical implementation and personalized care for NPC, especially in endemic areas.